Analisis Quality Function Deployment (Qfd) Untuk Pengembangan Sistem Electro Pneumatic Berbasis Programmable Logic Controller (Plc) Pada Mesin Semi Otomatis Tester Coding Battery - Chandra Aditya Luhur Wicaksono; Ansarullah Lawi; Yopy Mardiansyah (UNIB Press, 2025)
This research aims to develop a semi-automatic battery voltage testing machine using electro-pneumatic technology controlled by a Programmable Logic Controller (PLC) at PT VARTA Microbattery Indonesia. This machine is designed to enhance the efficiency and accuracy of testing lithium round cell 2/3 AA batteries, which were previously tested manually. The machine development utilizes the Quality Function Deployment (QFD) method, which identifies user needs through interviews and questionnaires, then translates them into technical characteristics within the system. The analysis using the House of Quality (HoQ) showed that the main priorities are testing accuracy, speed, ease of operation, and safety. This system integrates electro-pneumatic components, sensors, and PLC to control the machine's movements, ensuring a more efficient and consistent production process. The results indicate that the implementation of this semi-automatic machine can reduce the testing cycle time and improve battery production productivity.